(3YfGUQ h QehR Gdaf Gdjefj GdbOje ceONd ddESJdgGe aj GdJUhjQ GdeLSe (B= s The Elements and Symbols of Yemeni's ancient art an approach of inspiration in (sculptural {u2013} painting) - (3CfaGd YHOg SYjO GdeZdSs; (3CTQa ESeGYjd GdYQjfj (B: s; (3gGfj eMehO ajUd (B: s ((3GdbGgQI (B: s (3CfaGd YHOg SYjO GdeZdS (B: s, 2014)
(3YfGUQ h QehR Gdaf Gdjefi GdbOje ceONd ddGSJdgGe aj GdJUhjQ GdeLSe (B- (3COJ eJZjQGJ GdbQf GdYTQjf GdeJeKdI aj GdJbOe GdYdej h GdJcfhdhLj aj LejY eLGdGJ GdYdhe GdEfSGfjI Edi XghQ QDjI LOjOI aj Gdaf HTcd YGe h GdCSGdjH GdafjI HTcd NGU aJZjQJ QDjI GdafGf ef MjK JfGhdg ddTcd (B: (3GdeVehf (B: (3GdNGeI h GdJbfjI GdeSJNOeI OGNd GdYed Gdafj eeG CfJL CSdhH afi LOjO aj af eG HYO GdMOGKI jLeY eG Hjf GdCSdhHjf (B( (3GdfMJ h GdJUhjQ (B) (3h GdPi CWdb Ydjg GdJUhjQ GdeLSes
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI GdfhYjI (B- (3bSe GdJQHjI GdafjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdESJdgGes; (3GdJUhjQ GdeLSes; (3Gdaf Gdjefj GdbOjes